2011
DOI: 10.1016/j.carres.2011.08.031
|View full text |Cite
|
Sign up to set email alerts
|

NMR and conformational studies of linear and cyclic oligo-(1→6)-β-d-glucosamines

Abstract: The conformational behavior of a series of linear and cyclic oligo-(1→6)-β-D-glucosamines and their N-acetylated derivatives, which are related to fragments of natural poly-N-acetylglucosamine, was studied by theoretical molecular modeling and experimental determination of transglycosidic vicinal coupling constants 3JC,H and 3JH,H. Molecular dynamics simulations were performed under several types of conditions varying in the consideration of ionization of amino groups, solvent effect and temperature. Neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is quite possible that this conserved patch of residues initially binds PNAG and the force of biosynthesis moves the polymer in an extended conformation along the de-N-acetylation site to the IDL. Structural studies on β-1,6-GlcN oligomers show they have conformational freedom with the tendency to adopt stacked or helical structures (25). GlcNAc residues in −2 to +1 de-N-acetylation subsites show a stacked conformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible that this conserved patch of residues initially binds PNAG and the force of biosynthesis moves the polymer in an extended conformation along the de-N-acetylation site to the IDL. Structural studies on β-1,6-GlcN oligomers show they have conformational freedom with the tendency to adopt stacked or helical structures (25). GlcNAc residues in −2 to +1 de-N-acetylation subsites show a stacked conformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we designed a family of cyclic oligo‐(1→6)‐β‐ D ‐glucosamines consisting of two to seven monosaccharide units24, 25 and two cyclotetrasaccharides comprising both glucosamine and glucose residues 26. These cyclic oligomers differ from the well‐known cyclodextrins, which have more conformational flexibility27 but lack a distinct hydrophobic cavity. The presence of amino groups suitable for conjugation allows these cyclic oligosaccharides to be regarded as a new type of functionalized scaffolds for the development of multivalent glycoconjugates.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, Chizhov et al reported extensive studies concerning high resolution tandem mass spectrometry (ESI QqTOF) of cyclooligo-β-(1→6)- d -glucosamines, cyclooligo-β-(1→6)- d - N -acetyl-glucosamines (from two to seven Glc N or Glc N Ac residues, respectively, 19a , b – 24a , b , Figure 16) [70], and mixed isomeric β-(1→6)-linked cyclic tetrasaccharides of the Glc p 2 Glc pN 2 composition ( 25 and 26 , Figure 17) [71]. Synthetic details for the preparation, structural and conformational analysis of cyclo-β-(1→6)- d -glucosamines 19a , b – 24a , b were described in [72,73,74].…”
Section: First- and Second-order Mass Spectra Of Cyclic Oligosacchmentioning
confidence: 99%
“…Structural formulas of cyclooligo-β-(1→6)- d -glucosamines 19a – 24a and cyclooligo-β-(1→6)- d - N -acetylglucosamines 19b – 24b [70,72,73,74] (reproduced from [70] with permission of Springer Nature).…”
Section: Figurementioning
confidence: 99%